Analisa Pengaruh Gerak Makan Dan Putaran Spindel Terhadap Keausan Pahat Pada Proses Bubut Konvensional - Mohamad Miftakhul Rozaq; Iswanto Iswanto (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2017)
This paper discuss the effect of feeding motion and spindle rotation and also the relationship between feeding motion and spindle rotation on wear of tool in conventional lathe process. In this study the machining parameters are feeding motion (f) that varied at 0.12 mm/rev, 0.24 mm/rev and 0.35 mm/rev. With spindle rotation (n) that is 300 rpm, 650 rpm and 1000 rpm. While the cutting depth (a) is 0.5 mm. Then, the wearing edge of the tool was tested. The result of wear test in the edge of tool, show that (1) the greater the feeding motion the higher wear value of tool and the relationship is positively linear; (2) The larger the spindle rotation the lower wear value of tool will be and the relationship is negatively linear.